Evaluation of prognostic value of Fernandez scoring system on the management of ectopic pregnancy in the emergency room at Suez Canal University Hospitals, Egypt - Essa, Ahmed A.; Madny, Elham H.; Zayed, Osama M.; Elshaboury, Islam M.; Mahmoud, Bassma M. (International Surgery Journal, 2017)
Background: Ectopic pregnancy is a major cause of morbidity and mortality in reproductive-aged women, accounting for 9% of pregnancy-related deaths in the first trimester. Clinical prediction tools have been developed to aid management decision making. Fernandez et al “1991” developed a score based on gestational age, β-hCG level, progesterone level, abdominal pain, hemo-peritoneum volume, and hematosalpinx diameter. A score of less than 12 predicts more than 80% success with expectant or nonsurgical management. Aim of the study was to improve the outcome of patients with ectopic pregnancy attending the emergency room at Suez Canal University hospitals, Egypt. Methods: This is a descriptive (cross-sectional) study conducted on 62 patients diagnosed to have ectopic pregnancy in the emergency department in Suez Canal University Hospital. The patients were subjected to full assessment including full history, examination, investigation and Fernandez score. These data were collected in a questionnaire, interpretted using SPSS program and the score was calculated. Results: The study revealed that 48.8% of the patients were in the age group between 31-40 years. It was found that in 61 patients (98%) the decision matched using Fernandez score and experts’s opinion while only one patient was given a different decision. Using Fernandez score, 40 patients had results less than 12 which guided to conservative management and 22 patients had a score more than 12 which guided to operative management. Conclusions: It was found that Fernandez score has 100% sensitivity and 95.2% specificity.